Early rescue oocyte activation at 5 h post-ICSI is a useful strategy for avoiding unexpected fertilization failure and low fertilization in ICSI cycles - Xue, Lintao; Wang, Shikai; Wei, Pingpin; Liu, Haifang; Mao, Xianbao; Qin, Jie; Li, Yaoxuan; Zhang, Xiaohui; Li, Zhengda; Huang, Yueyue; Chen, Liangshi; Shi, Wen; et al. (Frontiers in Endocrinology, 2024)
Attempts to artificially activate unfertilized oocytes at 24 h post ICSI have generally resulted in poor outcomes. This study aims to explore a new strategy for early judgement and rescue activation of unfertilized oocytes at 5 h post ICSI to avoid unexpected fertilization failure or low fertilization in ICSI cycles. In this study, we found that the average time to Pb2 extrusion post-ICSI was 3.03±1.21 h, 95.54% of oocytes had extruded Pb2 before 5 h, and the sensitivity and specificity for monitoring Pb2 extrusion at 5 h by time-lapse imaging to predict fertilization were 99.59% and 99.78%, respectively. Early rescue activation of oocytes with no Pb2 extrusion resulted in acceptable fertilization and embryo developmental outcomes, in terms of the fertilization rate (75.00, 72.99%), 2PN fertilization rate (61.36, 56.93%), good-quality embryo rate (42.59, 50.00%), blastocyst formation rate (48.28, 46.03%), good-quality blastocyst rate (34.48, 33.33%), and oocyte utilization rate (36.36, 27.74%), for both UFF and ULF cycles. The clinical pregnancy, embryo implantation, and early miscarriage rates in the rescue oocyte activation group did not significantly differ from those in the Pb2 extrusion group. Fourteen unexpected fertilization failures and 20 low fertilization ICSI cycles were rescued and resulted in clinical pregnancy rates of 40.00% (4/10) and 57.14% (8/14), respectively. This study demonstrates that monitoring Pb2 extrusion by time-lapse imaging can accurately predict fertilization outcomes, suggesting that early rescue oocyte activation at 5 h post ICSI is an effective strategy for avoiding unexpected fertilization failure and low fertilization in ICSI cycles.